2018
DOI: 10.1039/c7nj03226a
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase extraction of ultra-trace levels of lead using tannic acid-coated graphene oxide as an efficient adsorbent followed by electrothermal atomic absorption spectrometry; response surface methodology – central composite design

Abstract: Tannic acid-coated graphene oxide as a novel and powerful adsorbent for the removal of lead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Since the adsorption isotherm fit Langmuir model much better this indicates that the surface sites on 3D GF-CS are homogeneous and the adsorption of SMZ is typically monolayer adsorption. The maximum monolayer adsorption capacity qmax was found to be 112.36 mg g −1 (Eftekhari et al, 2018). Other facts are Rl was less than 1 showing the adsorption was favorable.…”
Section: Adsorption Equilibrium Isothermmentioning
confidence: 92%
“…Since the adsorption isotherm fit Langmuir model much better this indicates that the surface sites on 3D GF-CS are homogeneous and the adsorption of SMZ is typically monolayer adsorption. The maximum monolayer adsorption capacity qmax was found to be 112.36 mg g −1 (Eftekhari et al, 2018). Other facts are Rl was less than 1 showing the adsorption was favorable.…”
Section: Adsorption Equilibrium Isothermmentioning
confidence: 92%
“…Due to ultra-trace concentration of Pb and Ni in human samples (urine and serum) and difficulty matrices in human biological samples, the sample treatment was used. For Examples, the solid phase extraction(SPE) [25], the magnetic dispersive micro-solid phase extraction (MD-μ-SPE) [26,27], the dispersive micro solid phase microextraction (D-SPME) [28], the needle hub in-syringe solid phase extraction (NHS-SPE) [29], and liquid-liquid microextraction (LLME) [30,31] were used. Among them, the dispersive micro solidphase extraction D-μ-SPE was mostly used for determination of heavy metals such as Ni and Pb in water and humans.…”
Section: Introductionmentioning
confidence: 99%
“…The CCD approach, as one of the most effective and widely applied designs of RSM, helps to evaluate multiple variables and interactions between these variables by performing fewer experiments and to determine the optimum process parameters (Ghelich et al 2019). Recently, it has been shown that CCD approach-based RSM is applied efficiently to provide the analysis and optimization of different chemical processes (Eftekhari et al 2018;Ghelich et al 2019;Khoshnamvand et al 2018;Mazaheri et al 2016;Srivastava et al 2015).…”
Section: Introductionmentioning
confidence: 99%